A multiple-method approach to studying childcare in an urban environment: the case of Accra, Ghana - Ruel, Marie T.; Armar-Klemesu, Margaret; Arimond, Mary (International Food Policy Research Institute, 2001)
This document summarizes findings from the Accra Urban Food and Nutrition Study (AUFNS) about the importance of care as an input to child nutrition and the relative contribution of various maternal and household resources to the provision of care.